Development of an Immersive Virtual Reality Learning Environment: Integrating Trauma-Informed Principles into Human Service Agency Settings. Issue 3 (18th August 2021) - Sturman, Steven; Sperlich, Mickey; Bakk, Louanne; Koury, Samantha
Abstract: This article details the creation of a Virtual Reality Learning Environment (VRLE) designed to educate students on how trauma-informed (TI) principles can be integrated into the physical environments of human service agencies. Virtual Reality (VR) technologies and characteristics that have the potential to improve student learning outcomes are reviewed. The integration of VR into a social work doctoral program is described, and the theoretical and pedagogical considerations that informed the creation of the TI VRLE are explored. Details of the process of developing and assessing the TI VRLE are discussed, together with lessons learned and directions for future research.